2009
DOI: 10.2105/ajph.2008.140459
|View full text |Cite
|
Sign up to set email alerts
|

Spousal and Alcohol-Related Predictors of Smoking Cessation: A Longitudinal Study in a Community Sample of Married Couples

Abstract: We investigated the longitudinal influence of spousal and individual heavy drinking and heavy smoking on smoking cessation among married couples. Couples' (N = 634) past-year smoking, alcohol problems, and heavy drinking were assessed. We used an event history analysis and found that spousal and one's own heavy smoking and one's own heavy drinking decreased the likelihood of smoking cessation. Heavy drinking and spousal behavior should be considered when developing public health interventions and policies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 17 publications
7
54
4
1
Order By: Relevance
“…This suggests that there may be additive effects if both partners smoke, possibly due to the combination of self-smoking and second-hand smoke exposure on ovulation, conception, and live birth (30). When effectiveness of smoking cessation interventions in couples was studied, several reports indicate that outcomes correlate with concordance of successful cessation for both partners (31)(32)(33). This paradigm has not been adequately studied in the preconception setting and may represent a missed opportunity in patients who are overall highly motivated (34).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there may be additive effects if both partners smoke, possibly due to the combination of self-smoking and second-hand smoke exposure on ovulation, conception, and live birth (30). When effectiveness of smoking cessation interventions in couples was studied, several reports indicate that outcomes correlate with concordance of successful cessation for both partners (31)(32)(33). This paradigm has not been adequately studied in the preconception setting and may represent a missed opportunity in patients who are overall highly motivated (34).…”
Section: Discussionmentioning
confidence: 99%
“…The positive support of partners had been showed to increase the success rate of smoking cessation programs (17 (18). In addition, smokers with non-smoker partners are more likely to quit smoking (9,19). Smoker partners may be less supportive during their spouse' s attempt to quit because they may think that they have to change their own smoking behaviors (20).…”
Section: Discussionmentioning
confidence: 99%
“…The smoking status of the partners is also a major determinant of success in smoking cessation efforts. Smokers are more likely to quit smoking with a non-smoker partner (9).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with increased risk for smoking in the general population (e.g., Dollar, Homish, Leonard, & Kozlowski, 2009;Homish & Leonard, 2005), close relationships with other smokers, including spouses or romantic partners, relatives, and peers, has been shown to be a risk factor for prenatal and postpartum smoking (Homish, Eiden, Leonard, & Kozlowski, 2012;Lu, Tong, & Oldenburg, 2001). Ma and colleagues (2005) found that, in a sample of pregnant women participating in a smoking cessation trial, having a partner who smokes was associated with smoking at time of delivery.…”
Section: Sociodemographic Factorsmentioning
confidence: 91%